NILAI-NILAI DIDAKTIS DALAM CERITA RAKYAT “PUTRI GUMBILI DENGAN BAMBANG HARUMAN” - Nidya Triastuti Patricia (UNDAS: Jurnal Hasil Penelitian Bahasa dan Sastra, 2019)
Indonesia has lots of folklores. Usually, folklore reflects value, believe, and tradition of the society. One of them is a folklore entitled “Putri Gumbili dengan Bambang Haruman” from South Kalimantan. This folklore contains didactics values that can be valuable lesson for the readers. That is why this study is done to answer some questions what are didactics values in “Putri Gumbili dengan Bambang Haruman” folklore. This study aims to describe didactics values in South Kalimantan folklore entitled “Putri Gumbili dengan Bambang Haruman”. This study uses content analysis approach. To collect the data, this study uses library method. Meanwhile, to analyse the data this study uses descriptive qualitative method. Didactics values which are analysed in this folklore “Putri Gumbili dengan Bambang Haruman” are ethics value, philosophy value, religious value, and intellectual value. Base on the result, in ethics values, there are respect to the ruler, well-behaved, to know one’s place and return a favor. In philosophy value, there are mantaining harmonious relationship between husband and wife, nurturing children, paying attention to other people and be respect, and do good deeds. In religious value, there are pray for goodness, do not commit suicide, and obey to our parent. And the last one is intelletual value, there are having knowledge, having skill, and clever.